2009
DOI: 10.1002/pmic.200800700
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of parthenogenetic and in vitro fertilized porcine embryos

Abstract: Proteomic data from embryos are essential for the completion of whole proteome catalog due to embryo-specific expression of certain proteins. In this study, using reverse phase LC-MS/MS combined with 1-D SDS-PAGE, we identified 1625 mammalian and 735 Sus scrofa proteins from porcine zygotes that included both cytosolic and membranous proteins. We also found that the global protein profiles of parthenogenetically activated (PA) and in vitro fertilized (IVF) zygotes were similar but differences in expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 79 publications
1
27
0
Order By: Relevance
“…It is also functionally linked to cell growth and its expression decreases concomitantly with the growth arrest during differentiation [45]. Most interestingly, it has been reported that TCP-1 is related to the growth and survival during pig embryo development, and it is more drastically upregulated in pig parthenogenetic embryos than in fertilized embryos [46]. In this study, TCP-1α was found expressed in all the three cell types (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…It is also functionally linked to cell growth and its expression decreases concomitantly with the growth arrest during differentiation [45]. Most interestingly, it has been reported that TCP-1 is related to the growth and survival during pig embryo development, and it is more drastically upregulated in pig parthenogenetic embryos than in fertilized embryos [46]. In this study, TCP-1α was found expressed in all the three cell types (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…Peptides corresponding to CAR protein (NP_001070948) were identified using TurboSEQUEST (Thermo Finnigan) and SEQUEST algorithm [20, 21], which was further validated using Scaffold software (Proteome Software, Portland, OR; version 3_00_02) [22]. Probabilities that the identified peptide and protein are correctly from CAR were >95% and >99%, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…State-of-the-art LC-MS/MS has been applied for a proteomic characterisation of both in vitro-fertilised (IVF) as well as parthenogenetic (PA) porcine embryos (Gupta et al 2009) 24 h after fertilisation or activation, respectively. As shown in mice, PA embryos are unable to develop to term except after genetic modification to correct for imprinted genes such as IGF2/H19 (Kono et al 2004).…”
Section: Proteomics From In Vitro-fertilised and Parthenogenetic Embryosmentioning
confidence: 99%